Germination Response of Fruit and Pod Vegetable Seeds Using Cow Manure Liquid Organic Fertilizer - Munia Nabilla Hutabarat; Asritanarni Munar; Sashikala Maruthai Pillai (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
The early growth of chilli peppers, long beans, green beans, and okra is often constrained by limited nutrient availability and a heavy reliance on chemical fertilizers, underscoring the need for effective, environmentally friendly organic liquid fertilizers. This study investigated the effects and optimal concentration of M2 (Panchagavya) liquid fertilizer on the early growth of these crops. M2 contains beneficial microbes, natural plant hormones, and essential nutrients that promote seed germination and root development. The fertilizer was prepared by fermenting organic matter for 30 days and tested in both laboratory (petri dish) and field experiments at six concentrations (0–5%) with three replications. Observed parameters included germination rate, root length, fresh and dry weight, pH, and electrical conductivity (EC), which were analyzed using ANOVA The results of this study indicate that M2 (Panchagavya) liquid fertilizer significantly enhances the early growth of chili peppers, long beans, green beans, and okra, improving germination rate, root length, and both fresh and dry biomass. M2 promotes root elongation and dry biomass accumulation through its beneficial microbes, natural plant hormones, and essential nutrients, thereby facilitating seedling germination and preparing young plants for efficient nutrient uptake. Optimal M2 concentrations vary by species: 1–2% for green beans and kale, and 4–5% for chillies and okra. This fertilizer is organic and environmentally friendly, reducing reliance on chemical fertilizers. It is recommended that users apply M2 at species-specific concentrations, particularly during germination and early vegetative growth stages, ensure a 30-day fermentation process to maintain fertilizer quality, and monitor plant growth to adjust dosages as needed.